Terrestrial heat flow and geothermal field characteristics in the Bide-Santang basin, western Guizhou, South China - Chen Guo (Energy Exploration & Exploitation, 2018)
Geothermal fields in coal-bearing strata significantly influence coal mining and coalbed methane accumulation and development. Based on temperature data from 135 coalfield exploration boreholes and thermophysical tests of 43 rock and coal samples from the Upper Permian coal-bearing strata of the Bide-Santang basin in western Guizhou, South China, the distribution of terrestrial heat flow and the geothermal gradient in the study area are revealed, and the geological controls are analysed. The results show that the thermal conductivity of the coal-bearing strata ranges from 0.357 to 3.878 W (m K) −1 and averages 1.962 W (m K) −1 . Thermal conductivity is controlled by lithology and burial depth. Thermal conductivity progressively increases for the following lithologies: coal, mudstone, siltstone, fine sandstone, and limestone. For the same lithology, the thermal conductivity increases with the burial depth. The present geothermal gradient ranges from 15.5 to 30.3°C km −1 and averages 23.5°C km −1 ; the terrestrial heat flow ranges from 46.94 to 69.44 mW m −2 and averages 57.55 mW m −2 . These values are lower than the averages for South China, indicating the relative tectonic stability of the study area. The spatial distribution of the terrestrial heat flow and geothermal gradient is consistent with the main structural orientation, indicating that the geothermal field distribution is tectonically controlled at the macro-scale. This distribution is also controlled by active groundwater, which reduces the terrestrial heat flow and geotemperature. The high geothermal gradient in the shallow strata (<200 m) is mainly caused by the low thermal conductivity of the unconsolidated sedimentary cover. The gas content of the coal seam is positively correlated with terrestrial heat flow, indicating that inherited palaeogeothermal heat flow from when coalbed methane was generated in large quantities during the Yanshanian period due to intense magmatic activity.